Endogenously segmented asset market in an inventory theoretic model of money demand - Jonathan Chiu (Bank of Canada, 2007)
This paper studies the effects of monetary policy in an inventory theoretic model of money demand. In this model, agents keep inventories of money, despite the fact that money is dominated in rate of return by interest bearing assets, because they must pay a fixed cost to transfer funds between the asset market and the goods market. Unlike the exogenous segmentation models in the literature, the timings of money transfers are endogenous. By allowing agents to choose the timings of money transfers, the model endogenizes the degree of market segmentation as well as the magnitude of liquidity effects, price sluggishness and variability of velocity. First, I show that the endogenous segmentation model can generate the positive long run relationship between money growth and velocity in the data which the exogenous segmentation model fails to capture. Second, I show that the short run effects of money shocks in an exogenous segmentation model (such as the linear inflation response to money shock, the liquidity effect and the sluggish price adjustment) are not robust. In an endogenous segmentation model, the equilibrium response to money shocks is non-linear and non-monotonic. Moreover, for large money shocks, there is no liquidity effect and no sluggish price adjustment.
Keywords: E31; E41; E50; 330; Transmission of monetary policy; Monetary policy framework; Geldpolitik; Kassenhaltungsansatz; Liquiditätseffekt; Transmissionsmechanismus; Theorie